Scorpion venom peptide SPVII promotes irradiated cells proliferation and increases the expression of the IL-3 receptor - Qiu, Yifang (BioMed Central, 2013)
BACKGROUND: The previous investigation demonstrated the radioprotective efficacy of peptides isolated from the venom of Buthus Martti Karsch. In this study, the effect of isolated scorpion venom peptide II (SVPII) on irradiated M-NFS-60 cells and mouse bone marrow mononuclear cells (BM-MNCs) was observed. The AlamarBlue cell viability assay, a colony-forming unit (CFU) assay, flow cytometry (FCM), immunofluorescence, and Western blotting were used to evaluate cell proliferation, cell cycle progression, and the expression of the IL-3 receptor (IL-3R) protein in non-irradiated and irradiated cells. RESULTS: Proliferation of irradiated M-NFS-60 cells was significantly accelerated by SPVII, and this effect was further enhanced by co-application of IL-3. Similarly, SPVII increased the number of BM-MNC CFUs and this proliferative effect was greater in the presence of SVPII plus IL-3. In addition, SPVII significantly altered cell cycle progression; SVPII enhanced the fraction of unirradiated M-NFS-60 cells in S phase and the fraction of irradiated M-NFS-60 cells arrested in G2/M. The expression of IL-3R protein by unirradiated M-NFS-60 cells was enhanced significantly by SVPII, and SVPII-induced IL-3R overexpression was 10-fold greater in irradiated M-NFS-60 cells. CONCLUSIONS: These results indicated the hematopoietic growth factor (HGF)-like effects of SVPII on irradiated cells, possibly mediated by upregulation of IL-3R.